Improvement of thermal stability of oyster (Crassostrea gigas) ferritin by point mutation. (1st June 2021) - Li, Han; Tan, Xiaoyi; Xia, Xiaoyu; Zang, Jiachen; El-Seedi, Hesham; Wang, Zhenyu; Du, Ming
Graphical abstract: Highlights: Point mutation in D120G could improve the thermal stability of oyster ferritin. The spherical shell of mutated ferritin can be kept well at 90 °C and below. The stability of oyster ferritin was promoted via the improved 3-fold interfaces. Abstract: Ferritin can be widely used as functional nanomaterial. But the physiological activity of ferritin can be damaged under excessive temperatures, which affect the self-assembly property. In this study, point mutation was produced in Asp 120 to Gly 120 of ferritin amino acid sequence and the heat resistance was improved significantly. The thermal denaturation temperature of mutated ferritin is 89.17 °C and has increased by 13 °C more than the wild-type oyster ferritin. The effect of thermal treatment on the denaturation, aggregation state, particle size and the structure of ferritin was not changed before 90 °C. The computational modeling and analysis indicated that mutated ferritin promotes the overall structural stability assembly via decreasing the interaction energies of 62 percent energies in 3-fold interface. Improving the thermal stability of oyster ferritin by point mutation enhances its applications as a food ingredient.